Identifikasi 8 Ashnaf Untuk Mendukung Akuntabilitas Lazis Dalam Pengentasan Kemiskinan Di Kecamatan Palengaan, Pamekasan - Pujayanti, Bella Apryani; Kusumaningtias, Rohmawati (Unversitas Islam Madura, 2021)
The purpose of this study was to identify 8 ashnaf to support LAZIS accountability in poverty alleviation in Palengaan District. The type of research used is qualitative research with a descriptive approach. The data in this study were obtained through interview, observation and documentation techniques. Sources of data used in the form of primary data sourced from interviews with the head of LAZIS, mustahik, muzakki, and local religious leaders, as well as secondary data from books, articles and journals. The results showed that there were only 4 groups of zakat recipients (ashnaf) identified in the LAZIS Panyeppen area, namely the indigent, the poor, amil, and fi sabilillah. In addition, from the results of the study it is also known that the distribution of zakat carried out by LAZIS Panyeppen has not fully helped the needs of the mustahik (the poor), this is because the nominal amount of zakat received by the poor is relatively lower than that received by other groups, so poverty in the Palengaan area has not been fully resolved.